Analysis Contribution and Effectiveness of Local Taxes Toward Original Regional Income at Bandung City - Nababan, Daniel; Gumilar Sambas Putra, Ivan; ., . (International Journal of Engineering and Technology, 2018)
This research is done to analyze the magnitude of contribution and effectiveness of local taxes toward original regional income at Bandung City. Method that used is descriptive analysis. Analysis result show that contribution of local taxes has contribution toward original regional income. The higher contribution of local taxes in 2013 is 82,763% and the lower in 2010 is 68,671%. Effectiveness of local taxes has effective toward original regional income. The higher effectiveness of local taxes in 2011 is 122,181% and the lower in 2016 is 78,210%. The results of data analysis use SPSS Version 20 showed that the result of hypothesis testing partially is contribution of local taxes has impact toward original regional income, and effectiveness of local taxes has impact toward original regional income. The result of hypothesis.Â Â